If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -9 = 3x + 11 Reorder the terms: -9 + 6x = 3x + 11 Reorder the terms: -9 + 6x = 11 + 3x Solving -9 + 6x = 11 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -9 + 6x + -3x = 11 + 3x + -3x Combine like terms: 6x + -3x = 3x -9 + 3x = 11 + 3x + -3x Combine like terms: 3x + -3x = 0 -9 + 3x = 11 + 0 -9 + 3x = 11 Add '9' to each side of the equation. -9 + 9 + 3x = 11 + 9 Combine like terms: -9 + 9 = 0 0 + 3x = 11 + 9 3x = 11 + 9 Combine like terms: 11 + 9 = 20 3x = 20 Divide each side by '3'. x = 6.666666667 Simplifying x = 6.666666667
| y-6=-2(x+2) | | (X-10)-4=12 | | 1.1y-(y-0.6)+0.3=0 | | 3x+3(x+5)=30 | | 3-5(4x+5)=78 | | 4(-3+1)=-10(x-4)-14 | | 4x^2-98+180=0 | | 4-7(1-2r)=15.5 | | -29-x=-7x+67 | | 7(x-3)=-3x+89 | | -7+3x-2x=17 | | 5y^5=20 | | 3500+1680x=175000+550x | | 8(3n-8)=8 | | 5.9-p=2 | | x-153=55+9x | | 6.3=7.0x | | -4.5(7x-6.5)=-23.5 | | 52-4x=10-10x | | 3x-2(x-3)+4(x+1)=-5 | | 2x-102-10x=42 | | -9(5-5.5k)=26.5 | | 14-8m= | | -77-10x=165+x | | 5ab*3= | | 5r-14=-44 | | 10x-1=6x+10 | | =9xy^2+6xy-5x | | 24+8y-16w= | | 2(7x-13)=16 | | 5x+(x+2)-3(x-4)=35 | | 5x+3+3x=83 |